Metabolic engineering: achieving new insights to ameliorate metabolic profiles in Withania somnifera - Patel, N.; Patel, P.; Khan, B. M. (Medicinal plants - recent advances in research and development, 2016)
Withania somnifera, commonly known as Indian ginseng, has been used for centuries in Ayurvedic system of medicine for its antitumor, antioxidant, antiaging, antiserotogenic, and antistress activities. The various medicinal properties of the plant are accredited to the steroidal lactones (withanolides) present in the plant. Withanolides are synthesized by diverting the metabolite flux away from the isoprenoid pathway by the reductive condensation of farnesyl diphosphate to squalene through the activity of the enzyme squalene synthase. This enzyme squalene synthase is a major branch point involved in the regulation of withanolides. Owing to low concentrations of these bioactive compounds in plant, large biomass is utilized for the preparation of medicinal formulations in pharmaceutical industries to fulfill the growing commercial demand. To protect Withania spp. from becoming an endangered species, the activity of squalene synthase has been well exploited. This chapter is focused on the engineering of isoprenoid biosynthetic pathway in W. somnifera by the introduction of squalene synthase gene to improve the yield of desired product.